âMADURA SPARKLING STARSâ: KONSEP KOTA WISATA MODERN DI KAWASAN PESISIR PASCA PEMBANGUNAN JEMBATAN SURAMADU DALAM MENINGKATKAN PEREKONOMIAN DI PULAU MADURA - Wafi, Moh. Kamalul; Ary, Vonda Bri Valdo; Kusumojati, Anindito (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2013)
Madura Island is an island with natural beauty tourism, arts and culture have a fairly abundant. Statistical BPS data in 2012 showed that the economy is still grows very slow in Madura. This is caused by low levels of accessibility Madura Island with national and activity centers in the region of East Java. In addressing these issues, the authors formulate the concept of locally -based industrial development that emphasizes the environmental balance and maintain cultural elements to achieve economic equality and sustainable form of Madura Sparkling Stars. Madura Sparkling Stars is a concept of modern tourist area located on the coast longest bridge. This concept emphasizes on empowering local communities to build economic stability through agriculture and fisheries in Madura, and make the area around the foot of the Suramadu as growth centers of Madura economy, and creates branding in an effort to enhance the attractiveness of the tourist to visit Madura.